Exchange Rate Assessment : Extension of the Macroeconomic Balance Approach - Isard, Peter (Occasional Papers; Occasional Paper ;, 1998)
The IMF's internal analysis of exchange rate issues has been guided by, and limited by, the conceptual and empirical frameworks that have emerged from the collective research of the economics profession. The research has provided several general approaches that are useful for assessing whether countries exchange rates seem broadly appropriate. One involves the calculation of purchasing power-party (PPP) measure or international competitiveness indicators. A second, known as the macroeconomic balance framework, focuses on the extent to which prevailing exchange rates and policies are consistent with simultaneous internal and external equilibrium over the medium run. Some recent extensions of the macroeconomic balance approach and the manner in which it is applied by the IMF staff are described in this paper.